Islamic Boarding School-Based School Human Resource Management In Shaping Student Character - Bahri, Syamsul (Jurnal Riset dan Inovasi Pembelajaran, 2024)
The purpose of this article is to investigate the methods of character development that can be used in extracurricular, cocurricular, and extracurricular activities in kindergarten–12 schools. This pesantren-based school has an advantage since it preserves the unique pesantren culture as an educational establishment whose primary goal is to inculcate religious principles to shape the morality of the country's youth. This study is a sort of qualitative research that is part of a descriptive research study that uses a case study methodology. The SMAN 1 WAJO is the study's location. Documentation, structured interviews, and participant observation were used to gather data. The study's findings indicate that: (1) SMAN 1 WAJO carefully planned its character development program, beginning with the creation of its vision, mission, and goals; (2) integrated character development through extracurricular, cocurricular, and intracurricular activities, including flagship programs like the English Club, Qiro 'Wal Hufadz, and the Yellow Book Study; and (3) monitored and evaluated through the following methods: (1) development of agreed-upon character value indicators; (2) compilation of assessment instruments; (3) summary of indicator achievements; (4) analysis and evaluation; and (5) follow-up.